The Anthroposcene of Weather and Climate Ethnographic Contributions to the Climate Change Debate - Sillitoe, Paul (Berghahn Books, 2021)
While it is widely acknowledged that climate change is among the greatest global challenges of our times, it has local implications too. This volume forefronts these local issues, giving anthropology a voice in this great debate, which is otherwise dominated by natural scientists and policy makers. It shows what an ethnographic focus can offer in furthering our understanding of the lived realities of climate debates. Contributors from communities around the world discuss local knowledge of, and responses to, environmental changes that need to feature in scientifically framed policies regarding mitigation and adaptation measures if they are to be effective.